Analysis of Language Registers on Facebook in the @Jual Beli HP Second Muntilan, Magelang, Jogja Group - Intannia Citra Septyarani; Alia Asti Chasanah; Jessica Adinda Putri (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
The rapid growth of social media has transformed online buying and selling interactions, giving rise to distinctive language variations within digital communities. This study aims to analyze the use of language registers in the Facebook group @Jual Beli HP Second Muntilan, Magelang, Jogja during the period of January–April 2026. A descriptive qualitative approach was employed, utilizing documentary data collection techniques through screenshots and notes from 12 posts containing registers out of a total of 150 posts. The analysis focused on the form, meaning, and function of registers based on sociolinguistic theory. The results showed that the 12 dominant registers took the form of abbreviations/acronyms (BU, TT, nego), loanwords (up, nett, no minus), and non-standard forms (orian), all of which are limited to the specific context of the online cell phone buying and selling community. The meanings of these registers encompass the condition of the item (fullset/batangan, no minus), pricing strategies (mahar, nego/nett), and alternative transaction methods (TT/BT), with instrumental (persuasive), informative (describing the condition), and regulatory (limiting bargaining) functions. These findings illustrate the eﬃciency of digital language in accelerating online economic interactions, as well as the adaptation of local communities to the dynamics of social media.